Existence of solutions for critical systems with variable exponents - Lalilia, Hadjira; Tas, Saadia; Djellit, Ali (Mathematical Modelling and Analysis, 2018)
In this work, we deal with elliptic systems under critical growth conditions on the nonlinearities. Using a variant of concentration-compactness principle, we prove an existence result.